Flame-retardant coating composition, refractory heat-insulating layer, and refractory heat-insulating sheet
A combination of acrylic and urethane resin emulsions with intumescent flame retardants and dispersants in a specific ratio forms a durable, flexible, and heat-insulating coating film that resists swelling and maintains performance in cold environments, addressing the issues of moisture absorption and peeling in existing water-based coatings.
Patent Information
- Application Number
- JP2023121411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
Existing water-based coating films used in fireproof paints suffer from moisture absorption leading to swelling, peeling, and poor appearance, especially in cold environments, due to high water absorption rates of acrylic resins commonly used as binders.
A flame-retardant coating composition combining acrylic and urethane resin emulsions with specific mass ratios, intumescent flame retardants, and dispersants, along with optional additives like polyhydric alcohols and inorganic reinforcements, to form a flexible, durable, and heat-insulating film.
The composition achieves excellent cold resistance, swelling resistance, and maintains flexibility even at low temperatures, preventing peeling and moisture ingress while providing effective flame retardancy and heat insulation.
Smart Images

Figure 2025018027000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to flame retardant coating compositions having intumescent flame retardants, fire resistant insulation layers, and fire resistant insulation sheets. [Background technology]
[0002] In the field of architecture, buildings are protected from flames and heat during fires by applying foamable fireproof paints to building materials such as steel frames and wall materials. When heated, the coating film of the foamable fireproof paint foams, and an expanded, non-combustible carbonized layer is formed, thereby exhibiting fireproof and heat-insulating performance. From the viewpoint of resource saving and reducing environmental load, water-based paints using water instead of solvents are desirable for this type of paint. For example, Patent Document 1 describes a water-based foamable fireproof paint containing a synthetic resin emulsion (A), a phosphorus compound (B), a polyhydric alcohol (C), and an anionic dispersant (D) having a polyoxyalkylene chain as essential components. In addition, a water-based composition using a resin emulsion has been developed as a coating agent for imparting flame retardancy to interior materials such as vehicle seats and floor mats. For example, Patent Document 2 describes a coating composition having a synthetic resin emulsion and a non-halogen flame retardant in which the surface of the non-halogen flame retardant particles containing phosphorus and nitrogen is coated with hydrophobic inorganic oxide fine particles. Patent Document 3 describes a flame-retardant resin composition containing a resin emulsion (a), ammonium polyphosphate (b), a water-absorbing porous material (c), and a low-molecular-weight dispersant (d). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-19394 A [Patent Document 2] JP 2007-186686 A [Patent Document 3] JP 2017-105928 A Summary of the Invention [Problem to be solved by the invention]
[0004] Coating agents such as foamable fireproof paints are often placed on the outermost surface of the object to which they are applied, and are therefore exposed to various environmental factors such as water, oil, acid, alkali, light, and temperature. Therefore, the coating film is required to have durability according to the environment in which it is used. For example, water-based coating agents have a high affinity with water. Therefore, when exposed to an environment in which moisture is present, the coating film is likely to absorb moisture and swell. If the coating film swells, peeling or poor appearance may occur. If the coating film peels off, moisture may penetrate through the peeled off coating, which may cause deterioration of the object. In addition, when considering use in cold regions, it is desirable for the coating film to maintain its flexibility even at low temperatures.
[0005] As described in Patent Documents 1 to 3, acrylic resin emulsions are described as resin emulsions, and acrylic resins are known as binder components of coating agents. Acrylic resins are excellent in hydrolysis resistance and chemical resistance, but have a relatively high water absorption rate. For this reason, in coating films that use acrylic resins as binder components, swelling due to water absorption is particularly problematic.
[0006] The present disclosure has been made in view of the above circumstances, and aims to provide a flame-retardant coating composition capable of forming a coating film having excellent cold resistance and swelling resistance, and exhibiting flame retardancy and heat insulation when heated. It is also an object of the present disclosure to provide a fire-resistant heat-insulating layer having excellent cold resistance and swelling resistance, and exhibiting flame retardancy and heat insulation when heated, and a fire-resistant heat-insulating sheet including the same. [Means for solving the problem]
[0007] (1) In order to solve the above problems, the flame-retardant coating composition of the present disclosure comprises an acrylic resin emulsion, a urethane resin emulsion, an intumescent flame retardant, and a dispersant, the glass transition point of the acrylic resin constituting the acrylic resin emulsion is −40° C. or lower, the urethane resin constituting the urethane resin emulsion has at least one of a carbonate bond and an ether bond, and the ratio of the solid content mass of the acrylic resin emulsion to the solid content mass of the urethane resin emulsion is 2:1 to 1:2.
[0008] In the flame-retardant coating composition of the present disclosure, both an acrylic resin emulsion and a urethane resin emulsion are used as binder components. The urethane resin has a lower water absorption rate than the acrylic resin. Therefore, by adding the urethane resin, the coating film is less likely to swell even when exposed to an environment where moisture is present. As a result, peeling of the coating film and poor appearance are less likely to occur. In addition, the glass transition point of the acrylic resin is -40°C or lower. This makes it possible to make the coating film flexible and maintain its flexibility even at low temperatures. Therefore, it is easy to apply to curved surfaces such as building materials and tanks, and can maintain a good condition even in cold regions. Furthermore, since the acrylic resin has excellent hydrolysis resistance and chemical resistance, the durability of the coating film is high. In addition, the urethane resin used has at least one of a carbonate bond and an ether bond. Carbonate bonds and ether bonds are less likely to hydrolyze than ester bonds. Therefore, even if the urethane resin is included, the durability of the coating film is less likely to decrease.
[0009] In the flame-retardant coating composition of the present disclosure, the ratio of the solid mass of the acrylic resin emulsion to the solid mass of the urethane resin emulsion is 2:1 to 1:2. That is, the mass ratio of the acrylic resin to the urethane resin in the coating film is 2:1 to 1:2. By setting the mass ratio of the acrylic resin to the urethane resin in this range, the advantages of using the acrylic resin and the advantages of using the urethane resin can be maximized. In this specification, the range of values such as ratios, "to", includes the values written before and after. In this way, according to the flame-retardant coating composition of the present disclosure, the water absorption rate of the coating film can be reduced and swelling can be suppressed while taking advantage of the advantages of the acrylic resin. As a result, peeling of the coating film and poor appearance can be suppressed. In addition, the intrusion of moisture from the coating film side can be suppressed, and deterioration of the object to which it is applied can be suppressed.
[0010] The flame-retardant coating composition of the present disclosure contains an intumescent flame retardant. When heated, the intumescent flame retardant decomposes to generate gas. This gas expands a carbonized layer in which an organic compound such as a binder resin is carbonized by combustion, forming an expanded non-combustible layer. This provides excellent flame retardant and heat insulating effects. As described above, the flame-retardant coating composition of the present disclosure can form a coating film that is excellent in cold resistance and swelling resistance, and exhibits flame retardancy and heat insulating properties when heated.
[0011] Incidentally, in the above Patent Documents 1 to 3, acrylic resin, urethane resin, etc. are described as resin components of the synthetic resin emulsion. However, these are merely listed as examples of binder components, and Patent Documents 1 to 3 do not describe or suggest the use of a specific acrylic resin and urethane resin in combination at a specific mass ratio in order to improve the swelling resistance of the coating film. For example, in the composition described in Patent Document 2, in order to reduce the slimy feeling when the coating film is wetted with water, the particle surface of the flame retardant is coated with hydrophobic inorganic oxide fine particles to exhibit water repellency. In the composition described in Patent Document 3, in order to suppress poor appearance when wetted with water, a water-absorbent porous material such as activated carbon, silica, and zeolite is added to reduce the contact between the flame retardant ammonium polyphosphate and water.
[0012] (2) In the above-mentioned configuration, the urethane resin constituting the urethane resin emulsion may have a water absorption rate of 20% or less. With this configuration, the swelling resistance of the coating film is further improved.
[0013] (3) In any of the above configurations, the intumescent flame retardant may have at least one of ammonium polyphosphate and melamine polyphosphate. With this configuration, the flame retardant decomposes at a desired temperature, and the generated gas can favorably foam and expand the carbonized layer.
[0014] (4) In any of the above configurations, the dispersant may be one or more selected from the group consisting of carboxylates, sulfates, sulfonates, and phosphates. This configuration can enhance the dispersibility of the powder components, fiber components, and the like that constitute the flame-retardant coating composition, and can improve the storage stability of the flame-retardant coating composition.
[0015] (5) Any of the above configurations may further include a polyhydric alcohol. The polyhydric alcohol is a raw material for forming a carbonized layer together with a binder resin, and when used together with an intumescent flame retardant, it strengthens the foamed carbonized layer and plays a role in maintaining the carbonized skeleton against foaming gas. With this configuration, a carbonized layer with favorable strength, thickness, etc. can be formed.
[0016] (6) In any of the above configurations, an inorganic reinforcing material may be further included. With this configuration, the strength of the coating film formed is increased, so that the coating film is less likely to crack when deformed by bending or the like. In addition, the carbonized layer that expands when heated is reinforced, so that it is less likely to crumble.
[0017] (7) Any of the above configurations may further include a foaming agent. With this configuration, the foaming and expansion reaction of the charred layer caused by the intumescent flame retardant can be further promoted.
[0018] (8) The fireproof heat insulating layer of the present disclosure is formed from the flame-retardant coating composition having any of the above configurations. The fireproof heat insulating layer of the present disclosure exhibits excellent flame retardant and heat insulating effects when heated. In addition, even when exposed to an environment in which moisture is present, it is not easily swollen. As a result, the fireproof heat insulating layer is less likely to peel off or have a poor appearance. In addition, the fireproof heat insulating layer is flexible and can maintain its flexibility even at low temperatures.
[0019] (9) The fireproof heat insulating sheet of the present disclosure includes a fireproof heat insulating layer having the above-mentioned configuration (8). The fireproof heat insulating sheet of the present disclosure has excellent workability because it is in a sheet form. In addition, the fireproof heat insulating layer is flexible and can maintain its flexibility even at low temperatures. Therefore, the fireproof heat insulating sheet of the present disclosure is easily applied to curved surfaces of building materials, tanks, etc., and is also suitable for use in cold regions. The fireproof heat insulating sheet of the present disclosure exhibits excellent flame retardant and heat insulating effects when heated. Here, the fireproof heat insulating layer is not likely to swell even when exposed to an environment containing moisture. As a result, the fireproof heat insulating layer is less likely to peel off or have a poor appearance. Effect of the Invention
[0020] The flame-retardant coating composition of the present disclosure can form a coating film that is excellent in cold resistance and swelling resistance, and exhibits flame retardancy and heat insulation when heated. The fire-resistant and heat-insulating layer and fire-resistant and heat-insulating sheet of the present disclosure are excellent in cold resistance and swelling resistance, and exhibit flame retardancy and heat insulation when heated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, the flame-retardant coating composition, the fire-resistant heat-insulating layer, and the fire-resistant heat-insulating sheet of the present disclosure will be described in detail. Note that the embodiments are not limited to the following embodiments, and may be modified or improved in various ways by those skilled in the art.
[0022] <Flame-retardant coating composition> The flame-retardant coating composition of the present disclosure comprises an acrylic resin emulsion, a urethane resin emulsion, an intumescent flame retardant, and a dispersant.
[0023] [Acrylic resin emulsion] The acrylic resin constituting the acrylic resin emulsion may be a polymer containing a structural unit derived from an acrylic acid ester or a methacrylic acid ester. In this specification, acrylic acid esters and methacrylic acid esters may be collectively referred to as (meth)acrylic acid esters. For example, homopolymers and copolymers of monomers selected from (meth)acrylic acid esters, copolymers of the monomers and other monomers, etc. may be mentioned. Alternatively, copolymers of polymers using (meth)acrylic acid esters and other polymers may be used. In addition, two or more types of emulsions having different polymer structures may be used as the acrylic resin emulsion.
[0024] The glass transition point (Tg) of the acrylic resin constituting the acrylic resin emulsion is -40°C or lower, and preferably -50°C or lower. The glass transition point may be measured, for example, using a differential scanning calorimeter (DSC). For commercially available products, the catalog value may be used. In the case of copolymers, the glass transition point may be calculated, for example, using the Fox formula. Therefore, an acrylic resin emulsion having a suitable glass transition point may be synthesized by adjusting the type and blending ratio of polymerizable monomers.
[0025] [Urethane resin emulsion] The urethane resin is obtained by the reaction of a polyol with a polyisocyanate. One of the causes of deterioration of the urethane resin is hydrolysis caused by the polyol. Various compounds such as polyester polyols, polyether polyols, and polycarbonate polyols are used as the polyol, but it is known that the ester bond derived from the polyol is more easily hydrolyzed than other bonds. Therefore, in the flame-retardant coating composition of the present disclosure, a urethane resin having at least one of a carbonate bond and an ether bond, which are relatively difficult to hydrolyze, is adopted as the urethane resin emulsion. That is, the urethane resin may have either a carbonate bond or an ether bond, or may have both. The emulsification method may be either a forced emulsification type using an emulsifier or a self-emulsification type in which a hydrophilic group is introduced into the polymer skeleton. Two or more emulsions having different polymer structures may be used as the urethane resin emulsion.
[0026] From the viewpoint of making the coating film less likely to swell, the water absorption rate of the urethane resin is preferably 20% or less. More preferably, it is 15% or less. In this specification, the "water absorption rate" is a value calculated as follows. First, the resin to be measured or a composition containing it is solidified to prepare a square sheet-shaped sample having a length of 20 mm, a width of 20 mm, and a thickness of 2 mm, and the mass is measured to obtain the "sample mass before immersion". Next, the prepared sample is immersed in warm water at 40°C for 350 hours. Then, the sample is taken out, the moisture on the surface is wiped off, and the mass is measured to obtain the "sample mass after immersion". Then, the water absorption rate is calculated by the following formula (I). Water absorption rate (%) = (sample mass after immersion - sample mass before immersion) / sample mass before immersion × 100 (I) The amount of the urethane resin emulsion is determined according to the amount of the acrylic resin emulsion. That is, in the flame-retardant coating composition of the present disclosure, the ratio of the solid content mass of the acrylic resin emulsion to the solid content mass of the urethane resin emulsion is 2:1 to 1:2. When the solid content mass of the urethane resin emulsion is less than 1 / 2 of the solid content mass of the acrylic resin emulsion, the amount of urethane resin is too small, so the effect of suppressing the swelling of the coating film is small. On the other hand, when the solid content mass of the urethane resin emulsion is more than twice the solid content mass of the acrylic resin emulsion, the amount of urethane resin is too large, so the coating film becomes hard and easily cracked.
[0027] [Intumescent flame retardants] As described above, when heated, the intumescent flame retardant decomposes and generates gas. This gas expands the carbonized layer in which organic compounds such as binder resins are carbonized by combustion, forming an expanded non-combustible layer. Examples of the intumescent flame retardant include ammonium polyphosphate and melamine polyphosphate. One of these may be used alone or in combination of two or more. For ammonium polyphosphate, from the viewpoint of improving water resistance and flame retardancy, it is preferable that the particle surface is coated with melamine resin or the like. The flame-retardant coating composition of the present disclosure may contain other flame retardants such as expanded graphite in addition to the intumescent flame retardant, as long as the effect of the present disclosure is not impaired.
[0028] When the total mass of the solid content of the acrylic resin emulsion and the urethane resin emulsion is 100 parts by mass, the content of the intumescent flame retardant is preferably 50 parts by mass or more from the viewpoint of realizing the desired flame retardancy. 80 parts by mass or more is preferable. On the other hand, if the content of the intumescent flame retardant is too high, the amount of gas generated increases, making it difficult to form a dense carbonized layer that exerts flame retardant and heat insulating effects. Therefore, the content of the intumescent flame retardant is preferably 500 parts by mass or less, and more preferably 300 parts by mass or less.
[0029] [Dispersant] The dispersant can improve the dispersibility of the powder components, fiber components, etc. that constitute the flame-retardant coating composition, and can improve the storage stability of the flame-retardant coating composition. Examples of the dispersant include carboxylates, sulfates, sulfonates, and phosphates. One of these may be used alone, or two or more may be used in combination.
[0030] When the total mass of the solid content of the acrylic resin emulsion and the urethane resin emulsion is 100 parts by mass, the content of the dispersant is preferably 1 part by mass or more from the viewpoint of realizing the desired dispersibility and storage stability. 3 parts by mass or more is preferable. On the other hand, if the content of the dispersant is too high, it may inhibit the formation of a carbonized layer and reduce the flame retardancy and heat insulation of the coating film. Therefore, the content of the dispersant is preferably 10 parts by mass or less, and more preferably 8 parts by mass or less.
[0031] [others] The flame-retardant coating composition of the present disclosure may contain other components in addition to the above-mentioned materials, as long as the effects of the present disclosure are not impaired. For example, polyhydric alcohols, inorganic reinforcing materials, foaming agents, crosslinking agents, pigments, etc. may be included.
[0032] Polyhydric alcohols are burned and carbonized, and therefore are suitable as a carbon source for forming a carbonized layer. When used together with an intumescent flame retardant, they strengthen the foamed carbonized layer and play a role in maintaining the carbonized skeleton against foaming gas. Examples of polyhydric alcohols include pentaerythritol, dipentaerythritol, tripentaerythritol, polypentaerythritol, trimethylolpropane, triethylene glycol, sorbitol, inositol, mannitol, glucose fructose, starch, cellulose, resorcinol, glycerin, trimethylolmethane, trimethylolpropane, diethylene glycol, propylene glycol, and hexamethylene glycol. These may be used alone or in combination of two or more.
[0033] When using polyhydric alcohol, its content should be 0.5 parts by mass or more when the total mass of the solid content of the acrylic resin emulsion and the urethane resin emulsion is 100 parts by mass, taking into consideration the formation of a carbonized layer. On the other hand, if the content of polyhydric alcohol is too high, the expansion of the carbonized layer may be inhibited. Therefore, the content of polyhydric alcohol should be 10 parts by mass or less, and further 5 parts by mass or less.
[0034] The use of inorganic reinforcing materials can increase the strength of the coating film and improve its durability against deformation such as bending. In addition, when inorganic reinforcing materials are contained, the carbonized layer that expands when heated is reinforced and becomes less likely to collapse. Therefore, inorganic reinforcing materials also contribute to improving flame retardancy and heat insulation. Examples of inorganic reinforcing materials include glass fiber, carbon fiber, and ceramic fibers such as silica, alumina, alumina silica, zirconia, and silicon carbide.
[0035] When using an inorganic reinforcing material, the content should be 1 part by mass or more when the total mass of the solid content of the acrylic resin emulsion and the urethane resin emulsion is 100 parts by mass, from the viewpoint of realizing the desired reinforcing property. 2 parts by mass or more is preferable. On the other hand, if the content of the inorganic reinforcing material is too high, it may hinder the formation of a carbonized layer and reduce the flame retardancy and heat insulation of the coating film. Therefore, the content of the inorganic reinforcing material should be 10 parts by mass or less, and further 5 parts by mass or less.
[0036] The use of a foaming agent can promote the foaming and expansion reaction of the carbonized layer caused by the intumescent flame retardant. The foaming agent is preferably a thermally decomposable foaming agent, and in order to effectively foam the layer, it is preferable that the foaming agent decomposes before the binder resin is carbonized. On the other hand, the foaming agent is required not to decompose during the process of forming the coating film, such as the process of drying the flame retardant coating composition. For this reason, it is preferable to select a foaming agent that decomposes at a temperature of 100°C or higher and 300°C or lower. Suitable foaming agents include azodicarbonamide, melamine cyanurate, guanidine, dicyandiamide, and sodium hydrogen carbonate.
[0037] When a foaming agent is used, its content should be 1 part by mass or more when the total mass of the solid content of the acrylic resin emulsion and the urethane resin emulsion is 100 parts by mass, taking into consideration the formation of a carbonized layer. On the other hand, if the foaming agent content is too high, the amount of gas generated increases, making it difficult to form a dense carbonized layer. In addition, the swelling resistance of the coating film may decrease. Therefore, the foaming agent content should be 20 parts by mass or less. Note that the form using a foaming agent has the advantage of promoting the foaming and expansion reaction of the carbonized layer, but has the disadvantage of increasing the water absorption rate of the coating film and decreasing the swelling resistance. For this reason, a form not using a foaming agent (content is 0 parts by mass) is also preferable.
[0038] The flame-retardant coating composition of the present disclosure may be produced, for example, by mixing and stirring an acrylic resin emulsion and a urethane resin emulsion in a predetermined ratio, adding a dispersant and stirring, and further adding an intumescent flame retardant, and if necessary, an inorganic reinforcing material, a polyhydric alcohol, a foaming agent, and the like, and stirring. The viscosity of the flame-retardant coating composition may be adjusted by adding water, etc. In cases where foaming occurs due to stirring, a defoaming agent, etc. may be added. However, most defoaming agents are easily combusted. Therefore, instead of adding a defoaming agent, it is preferable to defoam the composition by leaving it at rest under reduced pressure and stirring it.
[0039] <Fireproof insulation layer> The fire-resistant heat-insulating layer of the present disclosure is formed from the flame-retardant coating composition of the present disclosure. For example, the fire-resistant heat-insulating layer may be formed by directly applying the flame-retardant coating composition of the present disclosure to the surface of an object such as a building material, a fuel tank mounted on a vehicle, or a hydrogen tank, and drying the composition. Alternatively, the fire-resistant heat-insulating layer may be formed in a sheet form by applying the flame-retardant coating composition of the present disclosure to the surface of a substrate and drying the composition. The sheet-formed fire-resistant heat-insulating layer may be disposed on the surface of an object together with the substrate or after peeling from the substrate as a fire-resistant heat-insulating sheet described later. The flame-retardant coating composition may be applied by brushing, or by using a coating machine such as a blade coater, a bar coater, a die coater, a comma coater (registered trademark), or a roll coater, or by using a spray. Drying may be performed at a temperature of 80 to 150°C for several minutes to several tens of minutes.
[0040] The thickness of the fireproof and heat-insulating layer of the present disclosure may be adjusted as appropriate depending on the type of object to which it is applied, the location where it is placed, the form of use (presence or absence of other members such as a substrate), the required fireproof and heat-insulating properties, etc. For example, it may be 0.5 mm or more. On the other hand, in consideration of thinning and flexibility, it may be 3 mm or less. The fireproof and heat-insulating layer of the present disclosure expands when heated, but the thickness after expansion can be adjusted by the content of the intumescent flame retardant, etc. For example, the thickness after heating (expansion) can be about 1.5 to 5 times the thickness before heating.
[0041] <Fireproof and heat-insulating sheet> The fireproof heat insulating sheet of the present disclosure includes a fireproof heat insulating layer. That is, the fireproof heat insulating sheet of the present disclosure may be composed of only a fireproof heat insulating layer, or may be composed of a combination of another layer such as a substrate and a fireproof heat insulating layer. Examples of the latter form include a laminated sheet of a first layer and a fireproof heat insulating layer, and a laminated sheet of three or more layers in which a first layer, a second layer, a fireproof heat insulating layer, etc. are laminated. The laminated sheet may have an adhesive layer between the layers. For example, when the fireproof heat insulating sheet of the present disclosure is a laminated sheet, the substrate on which the fireproof heat insulating layer is formed is preferably a fiber sheet having heat resistance such as glass fiber or ceramic fiber. In addition, when a layer having a porous structure such as silica aerogel is laminated, the heat insulating property of the fireproof heat insulating sheet can be further improved. EXAMPLES
[0042] The present disclosure will now be described in more detail with reference to examples. In these examples, a fire-resistant heat insulating layer was formed from the flame-retardant coating composition of the present disclosure, and its swelling resistance, chemical resistance, and fire-resistant heat insulating properties were evaluated.
[0043] (1) Evaluation of swelling resistance and chemical resistance <Sample Production> [Examples 1 to 4, Comparative Example 2] First, the acrylic resin emulsion and the urethane resin emulsion were placed in a container in a predetermined mixing ratio and stirred with a stirring blade. Next, the polycarboxylic acid amine salt of the dispersant, the glass fiber of the inorganic reinforcing material, the polyphosphate ammonium powder of the intumescent flame retardant (the particle surface was coated with melamine resin), the polyhydric alcohol pentaerythritol (only Examples 2, 3, and Comparative Example 2 were mixed), and the foaming agent melamine cyanurate were added in order and stirred to prepare a flame-retardant coating composition. Next, the prepared flame-retardant coating composition was applied to the surface of a release film using a blade coater, and dried at 80°C for 30 minutes or more and at 100°C for 30 minutes. Then, the release film was peeled off to produce a fire-resistant heat-insulating layer with a thickness of 2 mm. The produced fire-resistant heat-insulating layer was cut into a square shape of 20 mm in length and 20 mm in width to prepare an evaluation sample.
[0044] Details of the resin emulsion used are as follows, and the amounts of the raw materials are shown in Table 1 below. The units of the amounts shown in Table 1 are parts by mass when the solid content mass of the acrylic resin emulsion is 100 parts by mass. Table 1 also shows the evaluation results of swelling resistance, chemical resistance, and fire and heat insulation properties, which will be described later. Acrylic resin emulsion A: AE610H acrylic emulsion manufactured by E-Tech Co., Ltd., Tg: -57°C. The water absorption rate of the coating film is 54.0%. Acrylic resin emulsion B: Sumikaflex (registered trademark) S-3950, an ethylene-acrylic-special ester emulsion manufactured by Sumika Chemtex Co., Ltd., Tg: -50°C. The water absorption rate of the coating film is 42.0%. Urethane resin emulsion: "Evaphanol (registered trademark) APC-55", a carbonate-based urethane resin emulsion manufactured by Nicca Chemical Co., Ltd. The water absorption rate of the coating is 13.4%.
[0045] [Comparative Example 1] An evaluation sample was produced in the same manner as the samples of Examples 1 to 4 and Comparative Example 2 above, except that no urethane resin emulsion was used as the binder, and only acrylic resin emulsion A was used.
[0046] [Table 1]
[0047] <Evaluation of swelling resistance> [Evaluation method] The evaluation sample was immersed in 40°C warm water for 350 hours, and the water absorption rate was calculated by the above formula (I). When the water absorption rate was less than 30%, the swelling resistance was evaluated as very good (indicated by a circle in Table 1 above), when the water absorption rate was 30% or more and less than 50%, the swelling resistance was evaluated as good, and when the water absorption rate was 50% or more, the swelling resistance was evaluated as poor (indicated by a cross in the same table).
[0048] [Evaluation Results] As shown in Table 1, it was confirmed that all of the samples of Examples 1 to 4, in which the blending ratio of acrylic resin to urethane resin was 2:1 to 1:2, had low water absorption and extremely good swelling resistance. In contrast, the sample of Comparative Example 1, which did not contain urethane resin as a binder, and the sample of Comparative Example 2, in which the blending ratio of acrylic resin to urethane resin was 4:1 and the acrylic resin content was excessive, had high water absorption and poor swelling resistance.
[0049] <Evaluation of chemical resistance> [Evaluation method] The samples for evaluation were coated with chemicals such as sulfuric acid aqueous solution, sodium hydroxide aqueous solution, and gasoline, and left for 48 hours, after which the appearance was visually observed. If the appearance of the sample did not change in response to any of the chemicals, i.e., if the sample showed neither deformation nor discoloration, the chemical resistance was evaluated as good (shown by a circle in Table 1 above), and if at least one of deformation and discoloration was observed in the sample in response to any of the chemicals, the chemical resistance was evaluated as poor (shown by an x in the same table).
[0050] [Evaluation Results] As shown in Table 1, it was confirmed that all of the samples of Examples 1 to 4 had good chemical resistance.
[0051] (2) Fire and heat insulation evaluation <Sample Production> The flame-retardant coating compositions prepared in the above (1) for producing the samples of Examples 1 to 4 and Comparative Examples 1 and 2 were each applied to the surface of a heat-resistant glass fiber nonwoven fabric substrate (Mitsubishi Paper Mills, Ltd., "GP100-TR", thickness 0.37 mm) using a blade coater. The substrate was then dried at 80°C for 30 minutes or more and at 100°C for 30 minutes to produce a sample of a fire-resistant heat insulating sheet consisting of "substrate / fire-resistant heat insulating layer."
[0052] <Fireproof and heat-insulating properties evaluation> [Evaluation method] A flame exposure experiment was carried out on the samples of the fireproof insulation sheet produced. In the flame exposure experiment, a propane gas burner flame was placed 35 mm away from the surface of the fireproof insulation layer, and after 10 minutes, the surface temperature of the substrate on the opposite side was measured. The higher the thermal insulation of the fireproof insulation layer, the lower the surface temperature of the substrate. The burner flame temperature was adjusted to 600°C at a position 35 mm away from the surface of the fireproof insulation layer.
[0053] [Evaluation Results] As shown in Table 1, it was confirmed that the samples of Examples 1 to 4 all had a substrate surface temperature of 220° C. or less and had the desired fire resistance and heat insulation properties. [Industrial Applicability]
[0054] The flame-retardant coating composition of the present disclosure, and the fire-resistant heat-insulating layer and fire-resistant heat-insulating sheet using the same are suitable for use in building materials such as steel frames and wall materials, fuel tanks mounted on vehicles, hydrogen tanks for fuel cell vehicles, battery housings for electric vehicles, and the like.
Claims
1. The composition comprises an acrylic resin emulsion, a urethane resin emulsion, an intumescent flame retardant, and a dispersant, the glass transition point of the acrylic resin constituting the acrylic resin emulsion is −40° C. or lower; The urethane resin constituting the urethane resin emulsion has at least one of a carbonate bond and an ether bond, A flame-retardant coating composition, characterized in that the ratio of the solid content mass of the acrylic resin emulsion to the solid content mass of the urethane resin emulsion is 2:1 to 1:
2.
2. 2. The flame-retardant coating composition according to claim 1, wherein the urethane resin constituting the urethane resin emulsion has a water absorption rate of 20% or less.
3. The flame retardant coating composition according to claim 1 , wherein the intumescent flame retardant comprises at least one of ammonium polyphosphate and melamine polyphosphate.
4. The flame-retardant coating composition according to claim 1 , wherein the dispersant comprises at least one selected from the group consisting of carboxylates, sulfates, sulfonates, and phosphates.
5. The flame retardant coating composition according to claim 1 , further comprising a polyhydric alcohol.
6. The flame-retardant coating composition according to claim 1, further comprising an inorganic reinforcing material.
7. The flame retardant coating composition of claim 1 further comprising a blowing agent.
8. A fire-resistant heat insulating layer formed from the flame-retardant coating composition according to claim 1.
9. A fire-resistant heat-insulating sheet comprising the fire-resistant heat-insulating layer according to claim 8.
Citation Information
Patent Citations
Coating composition and motor vehicle interior trim material
JP2007186686A
Foamable fireproofing paint
JP2008019394A
Flame retardant resin composition
JP2017105928A